Effects of isolation technique and conditions on the extractability, physicochemical and functional properties of pigeonpea (Cajanus cajan) and cowpea (Vigna unguiculata) protein isolates. I. Physicochemical properties - Mwasaru, Mwanjala A.; Muhammad, Kharidah; Bakar, Jamila; Che Man, Yaakob (Elsevier Science, 1999)
Physicochemical properties of pigeonpea and cowpea protein isolates were determined as a function of extraction technique and pH of the extracting medium. Protein extractability by the isoelectric point precipitation (IP) technique was positively correlated within the pH of the NaOH solution used in the pH range 8.5-12.5. The micellization (MP) technique extracted significantly (P < 0.05) less protein than the IP technique when extraction pH of the NaOH was 9.5 or higher, and 10.5 or higher from cowpea and pigeonpea, respectively. The subunit composition and electrical mobility of the isolates were not affected by extraction technique and pH conditions. However, it was observed that the IP isolate extracted at pH 12.5 had the lowest proportion of hydrophilic amino acids, suggesting that the pH of the extracting medium exerted a major influence on the hydrophilicity of the isolates. Pigeonpea MP isolate exhibited significantly (P < 0.05) higher exposed hydrophobicity than the IP isolates except for those extracted at pH 9.5 and 10.5. However, the cowpea MP isolate exhibited significantly lower exposed hydrophobicity than the IP isolate extracted at pH 8.5 but this was higher than the rest of the IP isolates. For IP isolates, an inverse relationship was apparent between the extraction pH and hydrophobicity. The MP isolates from both legume seeds were significantly lighter in colour than the corresponding IP isolates and, for the latter, the lightness value (L) was inversely correlated with extraction pH. Differential scanning calorimetry showed that the MP isolates exhibited higher transition enthalpy (ΔH) than the IP. For the IP isolates, ΔH decreased with increasing extraction pH.